A Study to Assess the Knowledge Regarding Nosocomial Infections Among Nursing Students of Selected Nursing Institutions in Mysuru - KN, Saraswathi (Research & Review: Management of Emergency and Trauma Nursing (e-ISSN: 2582-0494), 2022)
Background: Hospital-acquired infections (HAIs) are a major problem and challenge that hospitals around the world encounter. Nurses play a particular role in the prevention and control of HAIs as members of the healthcare team. The goal of this study is to analyze nursing students’ understanding of nosocomial infection in Mysuru’s selected colleges. Methodology: Due to the nature of the problem and the objectives of the study, the study takes a descriptive approach. 100 samples were selected by non-probability convenience sampling technique. The tool used for data collection consisted of proforma for structured knowledge questionnaire. Reliability of structured knowledge questionnaire was done using split half method and found r= 0.8 and the tools were found reliable. The pilot study was conducted to assess the feasibility of the study design. Based on the objectives and hypothesis of the study, the data were analyzed using descriptive and inferential statistics. Results: The mean score for nosocomial infection was 15.19, and the SD was 4.91. Over half of the students had poor knowledge. The knowledge of nursing students regarding nosocomial infections was correlated with their year of study.